Long-Term Follow-Up of Orthognathic Surgery in 19 Patients with Juvenile Idiopathic Arthritis - Henrik Krarup; Thomas Klit Pedersen; Paula Frid; Sven Erik Nørholt (eJournal of Oral Maxillofacial Research)
Objectives: Dentofacial deformity following juvenile idiopathic arthritis with temporomandibular joint involvement is associated with functional, aesthetic, and psychosocial impairment. Surgical treatment may involve combinations of orthognathic surgery. The aims of this retrospective study were to assess orofacial symptoms, functional and aesthetic status, and stability after orthognathic surgery.